USE OF HIGH-DEFINITION IMAGING FLOW CYTOMETRY AND A.I. TO ENUMERATE AND CHARACTERISE CIRCULATING TUMOUR CELLS (European Journal of Histochemistry)
The last decade has shone a spotlight on the field of liquid biopsies, a minimally invasive, yet data-rich approach for cancer diagnosis and management. There are many types of liquid biopsies including cerebrospinal fluid, blood, urine, saliva or pleural effusion. Liquid biopsies appear to have certain advantages when compared to tissue biopsies, including shorter time of acquisition, lower costs of sample isolation, monitoring tumour evolution, or real-time drug response. Growing evidence suggests that circulating tumour cells (CTCs; cancer cells that detach from a primary tumour and enter the bloodstream) reflect molecular features of cells within tumour masses. To date, very few CTC based tests have received FDA approval. In our laboratory we have explored the clinical utility of CTCs as prognostic or diagnostic biomarkers, using Image Stream, a benchtop, multispectral, imaging flow cytometer designed for the rapid acquisition of millions of cells (CYTEK). This imaging flow cytometry platform discriminates CTCs vs white blood cells (WBCs) in flow, objectively and statistically based on their appearance and immunostaining without the need of further enrichment. In our clinical samples we have used pan-cytokeratin staining to differentiate CTCs from CD45 positive WBCs. We have also used brightfield imaging to capture the cell morphology, as well as DRAQ5™ a general nuclear stain. CTCs were identified and quantified using the IDEAs software. This is a promising approach that does not require prior enrichment of cells of epithelial origin using EpCAM antibodies. In the future the combination of imaging (e.g. ultrasound, H&E staining), clinicopathological features and use of AI algorithms, may be able to distinguish CTCs, independent of specific marker expression, and drive a better prognostic outcome by tailoring treatment strategies to individual patients, optimizing treatment efficacy and minimizing side effects.